(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Correction: On 29th April 2015 the page numbers of this article were changed from 159-166 to 161-168. The present study was conducted to evaluate the impacts of aqua-drugs and chemicals on fish health and production in Mymensingh, Bangladesh from July 2013 to June 2014. Data were collected through personal contact, market survey, focus group discussion and participatory rural appraisal with fish farmers, associations and aqua-drug sellers. Fifty five different types of aqua-drugs and chemicals were recorded in the study area, among those, 20 types were widely used by the farmers for different fish disease treatment. It was recorded that renamycine, cotrim vet, ossi-c, polgard plus and timsen were used for the treatment of EUS in pangus, tilapia and koi which had an average recovery of 75-85%. For the treatment of edwardsiellosis in pangus and koi, farmers used potassium permanganate, timsen, polgard plus, geolite gold and renamycine which had an average recovery of 65-80%, and for the treatment of dropsy in tilapia, aquamycine, ossi-c and potassium permanganate were used which had an average of 80-85% recovery. Histopathology of gill and liver of fishes were almost normal in control ponds, whereas, in drugs treated ponds the organs had pathological changes like necrosis, pyknotic cells, hemorrhage, hypertrophy, lamellar missing, talengiactasis and vacuums. However, production of pangus, tilapia and koi was 12000 kg/acre, 15000 kg/acre and 14000 kg/acre in drug treated ponds respectively, whereas, it was 5000 kg/acre, 9000 kg/acre and 8000 kg/acre in non-treaded ponds respectively. Res. Agric., Livest. Fish.2(1): 161-168, April 2015